2020
DOI: 10.1159/000506645
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Ophthalmic Surgery Using a Freely Movable Arm Support Robot: Basic Experiment and Clinical Experience

Abstract: Introduction: The disadvantage of conventional armrests is the difficulty to adjust their height and position during surgery. Objectives: We investigated whether a freely movable armrest (FMA) that follows the surgeon’s arm is useful for reducing surgeon fatigue and arm tremors and for improving surgical accuracy. Methods: In the basic study, a corneal suture was placed in porcine eyes with FMA (FMA group) or without FMA (non-FMA group). The suture was intended to pass through two points. Tremor was quantified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In the 3 years prior to Goto et al’s publication, the EXPERT was used in 13 procedures on live patients and demonstrated no associated complications or mortality. In contrast to this, the previously discussed article by Okamura et al found that their FMA (freely moveable armrest) did not improve performance through reduction of hand tremor [ 21 ].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In the 3 years prior to Goto et al’s publication, the EXPERT was used in 13 procedures on live patients and demonstrated no associated complications or mortality. In contrast to this, the previously discussed article by Okamura et al found that their FMA (freely moveable armrest) did not improve performance through reduction of hand tremor [ 21 ].…”
Section: Discussionmentioning
confidence: 83%
“…As seen in Table 1 there was considerable variability in the methods of assessing baseline tremor and the units of measurement of baseline severity. Subjective microvascular tremor scale N: 2.4, E: 0.9* Nakano et al [14] Average pointing error + maximum error (μm) A: 70, M: >300 Yang et al [15] RMS for pointing task (μm) 112 Song et al [16] RMS for drift from a defined offset height (μm) L: 43.4, S: 36.0 Maclachlan et al [17] 3D maximum error (μm) N: 264, E: 318 Song et al [18] Tool tip motion towards target (μm) 1000 Zhang et al [19] Average deviation of tool tip (μm) 23.7 Yang et al [20] RMSE for holding tip still (μm) 90 Maximum error for holding tip still (μm) 240 Okamura et al [21] Mean tremor amplitude without FMA (pix) 699.4 Subjective tremor score (pts) 3 Csókay et al [22] Instrument tip movements (mm) 0.6 Therefore, it was not deemed feasible or reliable to calculate a mean baseline tremor (e.g., in Hz). Figure 2 highlights that approximately 89% of studies accessing the impact of tremors on performance in regards to surgical metrics reported an improvement in performance upon reduction and/or elimination of operator physiological tremor.…”
Section: Resultsmentioning
confidence: 99%
“…The subjective feelings of fatigue of the key members of the surgical team were assessed before and after surgery by using the “Jikaku‐sho shirabe” questionnaire (Table 1) [12] assembled by the Industrial Fatigue Research Committee of Japanese Occupational Health. It was designed to assess fatigue and has been widely used in Japan as a reliable tool to assess fatigue in workers [13, 14], including nurses and care workers [15, 16] and surgeons [17]. It consists of 25 subjective items for 5 factors (I: feeling of drowsiness; II: feeling of instability; III: feeling of uneasiness; IV: feeling of local pain or dullness; V: feeling of eyestrain).…”
Section: Methodsmentioning
confidence: 99%
“…15 A typical example of this type of robotic system is one that holds surgical instruments or rests human hands and arms. [16][17][18] For example, Rachinger and colleagues introduced a robotic system used as an instrument holder 13 based on a robot called Evolution 1; 19 the earlier robot had been used as an endoscope holder in transsphenoidal surgery with navigational support.…”
mentioning
confidence: 99%